Root anatomical parameters for identification of Fusarium wilt resistant and susceptible lines of pigeonpea - and SUSANTA BANIK, A.K. MANDAL*, P. SINHA (Indian Phytopathology, 2013)
Ten known Fusarium wilt resistant and six susceptible lines of pigeonpea were taken for the study of root morphological and vascular anatomical features of fifteen days old seedlings grown in plastic pot without inoculation. Resistant lines had comparatively fewer numbers of lateral roots as compared to susceptible lines. Microscopic observation of transverse section of tap root has shown some correlation between resistant traits and vascular anatomy. Resistant lines showed a tendency of higher protoxylem and metaxylem number and total xylem vessels cross-section area. However, some pigeonpea lines possessing less number of protoxylem and metaxylem showed resistant response. Number of protoxylem and metaxylem and their diameter were used as discriminate variable to develop a discriminant function to categorize the resistant and susceptible pigeonpea lines. Analysis of this variable using Discriminant function was developed for identification of pigeonpea lines resistant to Fusarium wilt: Discriminant function (y) = 0.042 (protoxylem number, x1) – 0.801 (protoxylem diameter, x2) + 0.090 (metaxylem number, x3) – 0.050 (metaxylem diameter, x4) + 0.001 (total protoxylem area, x5) – 0.064 (lateral root number, x8) – 1.762. This discriminant function could differentiate the Fusarium wilt resistant and susceptible lines of pigeonpea correctly up to the extent of 87.5%.